Two-stage technique in third molar autotransplantation: case report - Aécio Abner Campos PINTO JÚNIOR; Savana Márcia Alves COSTA; Joanna Farias da CUNHA; Andrea Clemente PALMIER (Faculdade São Leopoldo Mandic, 2018)
Tooth autotransplantation is an option for treating patients presenting early tooth loss. The teeth most commonly removed are the first molars, and their absence could lead to several oral health problems in patients. This transplant technique consists of the transposition and repositioning of a tooth from one area to another, in the same patient. Dental implants have high success rates, but tooth autotransplantation is less complex and less expensive, because the patient's own tooth is used. In the context of dental rehabilitation, tooth transplantation is focused on re-establishing masticatory function and esthetics. Success rates are variable, but in the majority of cases they exceed 80%. This article aims to report the case of a patient who underwent autotransplantation of the maxillary left third molar into the maxillary right first molar position. The surgical procedure was performed on two stages. After a 3-year clinical and radiographic follow-up period, a satisfactory result was achieved with the transplanted tooth presenting a healthy pulp and periodontal tissues, reestablishing the patient's function and esthetics.